Phylogenetic and Maturity Analyses of Sixty Soybean Genotypes Used for DNA Marker Development of Early Maturity Quantitative Trait Loci in Soybean - Tasma, I Made; Satyawan, Dani; Warsun, Ahmad; Yunus, Muhamad; Santosa, Budi (Jurnal AgroBiogen, 2011)
The Indonesian soybean productivity is still very low with the national average of 1.3 t/ha. One means to improve national soybean productivity is by manipulating harvest index by cultivating very early maturing soybean cultivars. Development of early maturing soybean cultivars can be expedited by using marker-aided selection. The objective of this study was to select parental lines having contrasted maturity traits and selected parents must be genetically distance. The parents then were used to develop F2 populations for detecting early maturity QTL in soybean. Maturity tests of 60 soybean genotypes were conducted at two locations, Cikeumeuh (Bogor) and Pacet (Cianjur) using a randomized block design with three replications. Genomic DNA of the 60 genotypes were analyzed using 18 SSR markers and genetic relationship was constructed using the Unweighted Pair-Group Method Arithmatic through Numerical Taxonomy and Multivariate System program version 2.1-pc. Results showed that the 60 genotypes demonstrated normal distribution in both locations for days to R1 (32-48d), days to R3 (35-55d), days to R7 (75-92d), and days to R8 (78-99d). Four early maturing genotypes and three late genotypes were obtained. Total SSR alleles observed were 237 with average allele per locus of 12.6 (3-29), and average PIC value of 0.78 (0.55-0.89). Genetic similarity among genotypes ranges from 74.8-95%. At similarity level 77% divided the genotypes into six clusters (the four selected early maturing genotypes located in clusters III and IV, while the three late genotypes located in cluster II). Based on maturity data, pubescent color, and phygenetic analysis seven parents were selected (four early maturing genotypes B1430, B2973, B3611, B4433 and three late genotypes B1635, B1658, and B3570). Twelve F2 populations were developed with the aid of SSR markers Satt300 dan Satt516. Two of the populations will be used to develop DNA markers for earliness in soybean.